Pemanfaatan Fasilitas Pelayanan Kesehatan Dalam Pertolongan Persalinan Di Puskesmas Sungai Piring Utilization of Health Care Facilities in Childbirth Assistance At The Sungai Piring Health Center - Aprita Dewi; Nurlisis Nurlisis; Nur' Afni (STIKes Hang Tuah Pekanbaru, 2020)
The Strategic Plan of the Ministry of Health for 2015-2019 establishes childbirth in health service facilities (fasyankes) as an indicator of maternal health efforts. This study aims to determine the utilization of health care facilities in childbirth assistance at Sungai Piring Health Care. The method in this research was qualitative with interviews, documentation, photos, videos, and observations. This study used primary data types and secondary data. Analysis of the data used descriptive analysis based on data collected through data collection techniques. The results of the study obtained priority problems namely low labor in health facilities 21%, The alternative problem solving is to increase education in the integrated service center (Posyandu), classes of pregnant women, visits to P4K homes, partnerships midwife and traditional birth attendants, Up-to-date knowledge for health workers, technical guidance by the person in charge of the Mother and Child Healthy (KIA) program to the midwife in the village and the refreshment of Posyandu cadres. The utilization of health care facilities in childbirth assistance is still not running by the performance standards of the KIA/ contraceptive care service unit. An effort that must be conducted to increase the competence of midwife, persuasive approaches, and improving the quality of Ante Natal Care (ANC) so that pregnant women who did the ANC in the public health care could be delivered in the health care, as well as expand the authority of the midwife in charge to promote childbirth services.